2023
DOI: 10.1002/dta.3533
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of new psychoactive substances in hair and urine samples of individuals subject to drug testing in driving license regranting—A toxicological perspective

Abstract: In recent years, numerous new psychoactive substances (NPS) have emerged on the illicit drug market. The assumed non‐detectability of these drugs is often a key motivation for individuals subject to drug testing, such as those in driving license regranting programs. In these programs, NPS are not routinely tested for, and thus, subjects who have to prove abstinence from common drugs of abuse might switch to NPS to avoid positive drug tests. The aim of the study was to determine the frequency of these substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…A larger German DUID study on 2539 serum samples reported an SC positivity rate of 10.8% 11 . In an abstinence control program for driver's license regranting, research by Hutter et al 26 determined SCs in 13% of 97 hair samples, and Fels et al 27 found SCs in 7% of 577 hair samples and 0.4% in 460 urine samples, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…A larger German DUID study on 2539 serum samples reported an SC positivity rate of 10.8% 11 . In an abstinence control program for driver's license regranting, research by Hutter et al 26 determined SCs in 13% of 97 hair samples, and Fels et al 27 found SCs in 7% of 577 hair samples and 0.4% in 460 urine samples, respectively.…”
Section: Introductionmentioning
confidence: 98%